Race, Labor, and Civil Rights : Griggs versus Duke Power and the Struggle for Equal Employment Opportunity - Smith, Robert Samuel, 1969- (Book collections on Project MUSE., 2008)
In 1966, thirteen black employees of the Duke Power Company's Dan River Plant in Draper, North Carolina, filed a lawsuit against the company challenging its requirement of a high school diploma or a passing grade on an intelligence test for internal transfer or promotion. In the groundbreaking decision Griggs v. Duke Power (1971), the United States Supreme Court ruled in favor of the plaintiffs, finding such employment practices violated Title 7 of the Civil Rights Act of 1964 when they disparately affected minorities. In doing so, the court delivered a significant anti-employment discriminati.